Beyond the Clinical: Branding as a Posthuman Interface in Patient Decision-Making - Rizal, Muhamad; ., Indasah; Subiyanto, Ahmad Arman; Subiyanto, Ahmad Arman; Sari, Nafi Septi Mekar (Journal of Posthumanism, 2025)
This study adopts a posthuman perspective to review patients’ decision making in the context of public hospitals drawing on the interplay of branding and differentiation and positioning. Using a quantitative approach with SEM-PLS on a sample of 99 patients at RSUD Karsa Husada Batu, Indonesia, the differentiation was found to have a direct effect on patient decisions, while positioning had an effect when moderated by branding. Branding is a techno-cultural signal produced by data, algorithms, and network patients, not just an identity, that has implications on our present findings. The investigation considered the digital, and some of the realization activities, to have symbolic mediation diminished, between the physical experience and the reality. These findings encourage a change from a linear marketing orientation, to an interaction-based ecosystem, in which patients are posthuman decision actors in a complex and digitalised environment.